Research progress on anti-food allergy and immunomodulatory properties of lactic acid bacteria - QIN Mengchun, ZHANG Lingfang, HU Shun'an, MA Lin, YIN Liying, LI Dan, DUAN Cuicui (Zhongguo niangzao)
Lactic acid bacteria are food-safe microorganism and had a variety of probiotic functions, such as regulating intestinal microecological balance, anti-tumour, antioxidant, immunomodulation, anti-food allergy, etc. Lactic acid bacteria have thus become a hot research topic in medicine and industry in recent years. In addition, intestinal flora plays an important role in the sensitisation mechanism of food allergy, which makes it possible to use lactic acid bacteria to prevent or treat food allergy. The sensitisation mechanisms of food allergy were described and the anti-food allergy mechanisms of lactic acid bacteria based on the sensitisation mechanisms were summarized. The immunomodulatory mechanism and adhesion of lactic acid bacteria were also discussed, aiming to provide certain theoretical references for the development of lactic acid bacteria-based anti-food allergy and immunomodulatory function foods and resource utilization of lactic acid bacteria.